2004
DOI: 10.1562/ra-020r.1
|View full text |Cite
|
Sign up to set email alerts
|

The Complex of Apomyoglobin with the Fluorescent Dye Coumarin 153¶

Abstract: Understanding a protein's dielectric response requires both a theoretical model and a well-defined experimental system. The former has already been proposed by Song (J. Chem. Phys. 116, 9359 [2002]). We suggest that the latter is provided by the complex of coumarin 153 (C153) with apomyoglobin (ApoMb). C153 has been exhaustively studied and has proven to be an excellent probe of the solvation dynamics of polar solvents. Myoglobin is one of the most thoroughly studied proteins.Myoglobins from a wide range of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 60 publications
5
26
0
Order By: Relevance
“…While DANCA and ANSDMA are both capable of charge transfer in the excited state, coumarin 153 is exquisitely inert, which is one of the reasons it has been so extensively employed as a probe of solvation. 57,[62][63][64][65][66][67][68][69][70][71][72][73] (The DANCA experiments used an excitation wavelength of 345 nm. Novaira et al have observed that both LE and CT emission can be observed in reverse micelles at 330 nm.…”
Section: L(t) )mentioning
confidence: 99%
“…While DANCA and ANSDMA are both capable of charge transfer in the excited state, coumarin 153 is exquisitely inert, which is one of the reasons it has been so extensively employed as a probe of solvation. 57,[62][63][64][65][66][67][68][69][70][71][72][73] (The DANCA experiments used an excitation wavelength of 345 nm. Novaira et al have observed that both LE and CT emission can be observed in reverse micelles at 330 nm.…”
Section: L(t) )mentioning
confidence: 99%
“…As mentioned above, some species of coumarin derivative interact with myoglobin, according to the literature reported previously [25]. On these grounds, we investigated myoglobin recognition abilities of 1a and 1b by fluorescence spectroscopy.…”
Section: Guest-binding Behavior Of Coumarin-appended Cyclophanesmentioning
confidence: 70%
“…Among them, coumarin and its derivatives take advantages in a viewpoint of their high quantum yield, thermal stability, and less toxicity [24]. In particular, a certain coumarin derivative was known to exhibit binding affinity toward myoglobin [25]. In the series of our research on fluorophore-appended cyclophanes, we began to develop coumarin-appended cyclophanes with the aim of sensing for specific proteins.…”
Section: Introductionmentioning
confidence: 99%
“…CZE was used to study b-amyloid and its aggregation [275], botulinum neurotoxin B light chain activity [276], nonenzymatic posttranslation modifications on BSA [277], aminoacyl-tRNA synthetase localized in cell nucleus [278], protein-protein interactions [279], aggregation and denaturation of antibodies [280], glycosylation of murine erythropoietin [281], PEGylation of proteins [282], glutamine deamidation in proteins [283], complexation of apomyoglobin with Coumarin 153 [284], reaction of FQ with ovalbumin [285], interaction of GFP with calcium [286], noncovalent complexation in myoglobin [287], DNA-protein interactions [288][289][290], binding fucoidan to antithrombin [291], retinoic acid to b-lactoglobulin B [292], and binding phospholipid and glycosaminoglycan to human b 2 -glycoprotein [293].…”
Section: Other Proteinsmentioning
confidence: 99%